Anodic and Cathodic Platinum Dissolution Processes Involve Different Oxide Species - Fuchs, Timo; Briega-Martos, Valentín; Drnec, Jakub; Stubb, Natalie; Martens, Isaac; Calle-Vallejo, Federico; Harrington, David A.; Cherevko, Serhiy; Magnussen, Olaf M. (Angewandte Chemie International Edition, 2023)
The degradation of Pt-containing oxygen reduction catalysts for fuel cell applications is strongly linked to the electrochemical surface oxidation and reduction of Pt. Here, we study the surface restructuring and Pt dissolution mechanisms during oxidation/reduction for the case of Pt(100) in 0.1 M HClO4 by combining operando high-energy surface X-ray diffraction, online mass spectrometry, and density functional theory. Our atomic-scale structural studies reveal that anodic dissolution, detected during oxidation, and cathodic dissolution, observed during the subsequent reduction, are linked to two different oxide phases. Anodic dissolution occurs predominantly during nucleation and growth of the first, stripe-like oxide. Cathodic dissolution is linked to a second, amorphous Pt oxide phase that resembles bulk PtO2 and starts to grow when the coverage of the stripe-like oxide saturates. In addition, we find the amount of surface restructuring after an oxidation/reduction cycle to be potential-independent after the stripe-like oxide has reached its saturation coverage.
CRIS-Team Scopus Importer:2024-12-16
Keywords: catalyst degradation; density functional calculations; online mass spectrometry; platinum oxidation; X-ray diffraction